2016
DOI: 10.1097/mib.0000000000000652
|View full text |Cite
|
Sign up to set email alerts
|

Low Fecal Calprotectin Correlates with Histological Remission and Mucosal Healing in Ulcerative Colitis and Colonic Crohnʼs Disease

Abstract: Low FC correlates well with histological remission and mucosal healing in colonic inflammatory bowel disease and is thus a clinically useful surrogate for inflammatory activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
57
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(62 citation statements)
references
References 42 publications
3
57
0
2
Order By: Relevance
“…Several groups have shown that FC levels correlate with endoscopic disease activity in CD patients 5,29,30 , but few studies have assessed the correlation between FC levels and mucosal lesions in the deep small intestine in CD. In the present study, a moderate agreement was found between FC levels and small bowel CD.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have shown that FC levels correlate with endoscopic disease activity in CD patients 5,29,30 , but few studies have assessed the correlation between FC levels and mucosal lesions in the deep small intestine in CD. In the present study, a moderate agreement was found between FC levels and small bowel CD.…”
Section: Discussionmentioning
confidence: 99%
“…Zittan et al . [ 20 ] also demonstrated that the FC test highly correlated with clinical symptoms in UC but less so in colonic CD. However, Tursi et al .…”
Section: Discussionmentioning
confidence: 99%
“…[ 31 34 ] Therefore, monitoring FC may decrease the need for invasive procedures to distinguish patients with quiescent disease who develop functional symptoms from those with active inflammation and who may benefit from escalation in therapy. [ 20 ] FC is a reliable, simple, inexpensive, and safe test that correlates closely with endoscopic findings in UC. [ 35 36 ] It provides more objective results than fecal microscopy and bypasses the difficulty of identifying stool leukocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In ulcerative colitis, a fecal calprotectin > 250 μg/g indicated active disease (Mayo subscore > 0) with a sensitivity of 71.0% and a specificity of 100% [3] . Low fecal calprotectin levels correlated well with histological remission (Geboes score < 3.1) and mucosal healing [19] . In addition, fecal calprotectin measurement can be used to identify patients with increased risk of relapse after 6 and 12 months and to predict histological healing [20] .…”
Section: Discussionmentioning
confidence: 84%